FAKTOR – FAKTOR YANG MEMPENGARUHI AUDIT DELAY PADA BANK KONVENSIONAL - Verene Barbie; Luh Putu Puji Trisnawati (POLITEKNIK LP3I JAKARTA, 2024)
Companies with strong financial conditions tend to complete their financial statement audits more quickly to enhance investor confidence. Investors need timely financial statements to assess business activities, performance, and profit potential over multiple periods. When there is a delay in publishing financial statements, it may hinder investors' decision-making and affect their perception of the company's financial condition. In conducting business activities, every company requires banking institutions. Banks have an important role in the economy and society, especially as a driver of fund flows and supporting economic activities. Banks are the link between those who have more funds (such as savers) and those who need funds (such as entrepreneurs or individuals who need loans). Using a quantitative research method, this study aims to analyze the impact of profitability, solvency, liquidity, and company size on audit delay in banks with core capital (KBMI) levels 3 and 4, as listed on the Financial Services Authority (OJK) website for the period 2017-2022. The quantitative method involves using secondary data, specifically financial statements, as the research data source. The sample was selected through non-probability sampling and purposive sampling techniques, resulting in 14 companies with a total of 84 data points. This study employs multiple linear regression analysis. Based on partial test results (t-test), it shows that solvency and liquidity do not affect audit delay, with significance values of 0.423 and 0.056, respectively, both of which are greater than 0.05. On the other hand, profitability and company size significantly influence audit delay, with significance values of 0.011 and 0.003, both of which are less than 0.05. The F-test, with a significance value of 0, indicates that profitability, solvency, liquidity, and company size collectively impact audit delay.